The mesolimbic system and the loss of higher order network features in schizophrenia when learning without reward - Martin, Elizabeth; Chowdury, Asadur; Kopchick, John; Thomas, Patricia; Khatib, Dalal; Rajan, Usha; Zajac-Benitez, Caroline; Haddad, Luay; Amirsadri, Alireza; Robison, Alfred J.; Thakkar, Katherine N.; Stanley, Jeffrey A.; et al. (Frontiers in Psychiatry, 2024)
The current investigation explored a potential loss of network features in schizophrenia patients and controls (n=78; 46 SCZ, 18 ≤ Age ≤ 50) while participants engaged in associative learning without reward-related contingencies. Network features were defined as follows: First, for each task condition, we estimated 2nd order undirected functional connectivity for each participant (uFC, based on zero lag correlations between all pairs of regions). These 2nd order features represent the task/condition evoked synchronization of activity between pairs of brain regions. Next, in each of the patient and control groups, the statistical relationship between all possible pairs of 2nd order features were computed. These higher order features represent the consistency between all possible pairs of 2nd order features in that group and embed within them the contributions of individual regions to group structure. This analytical goal was linked to a recent circuit-based integrative model suggesting that a synergy between learning and reward circuits is crucial in learning, but lost in schizophrenia. A notable prediction was that such a loss would be observed even during learning without reward-related contingencies. Thus, a test of the integrative model was whether we observed a loss of network features between the brain's subcircuits for a) learning (including the hippocampus and prefrontal cortex) and b) reward processing (specifically constituents of the mesolimbic system that included the ventral tegmental area and the nucleus accumbens. From inter-group differences (SCZ ≠ HC) in higher order features, respective contributions of individual brain regions to the (potential) loss of group network features were quantified. Two effects emerged: 1) SCZ were characterized by a loss of higher order features during multiple task conditions (encoding and retrieval of associations). 2) Nodes in the mesolimbic system were over-represented in this loss of higher order features. These methods and results are consistent with the idea that schizophrenia is characterized by a loss of synergy between cognition and reward subcircuits, with elements of the mesolimbic system heavily implicated even when learning without contingencies. The findings motivate a renewed appraisal of the relationship between reward and cognition in schizophrenia.